Globalisation, Post-Colonialism and Museums - Harris, Jennifer (International Committee for Museology-ICOFOM, 2008)
Abstract: Globalisation, Post-Colonialism and Museums Jennifer Harris's Australia Globalisation in museums emerges from a long history of their engagement with diverse cultures. Contemporary debates about globalisation need to be understood as emerging from post-colonial issues about allowing the lives and voices of others to be represented in the museum space. The central element of globalisation is intense interconnectedness made possible by worldwide communication technology. It should be understood in museums, therefore, not as something radically new, but as offering an intensification of the processes of dialogue that were begun some decades ago as museums responded to post-colonial challenges. This paper examines the twin globalising forces of homogenisation and local resistance to it by looking at the example of the famous Benin Bronzes from West Africa and their recent exhibition in Paris at the Muse du Quai Branly. The bronzes were exhibited in an aesthetic framework rather than in political and historical contexts and provoked much criticism. If museums wish to respond to globalisation they need to respond to such criticisms and see them as a positive and potentially productive opportunity.